Land Conflicts and Violence in the Brazilian Amazon Region (Global Journal of Human-Social Science, 2019)
The Brazilian Amazon region is the scene of the greatest number of deaths resulting from land disputes in the democratic period (1985 onwards). Such territorial conflicts occur at the time of the growing concentration of this natural resource in the hands of a few owners, whether of the old landowners or the modern structure of agribusiness. Data will be analyzed on agrarian violence, pointing out its main victims and the perpetrators in this type of conflict. The concentration of land has a new face with the acquisition by transnational conglomerates and countries interested in the food sovereignty of their populations, where large tracts of land are purchased to produce food and energy.
Keywords: federalism; re-federalization; resource control; political restructuring; nigeria